Masters of Manufacturing Carl R. Deckard.
This is the tenth annual installment in a series we call Masters of Manufacturing. In these articles, we honor a distinguished figure in manufacturing technology, and by doing so, we hope to remind readers that a career of great achievement in manufacturing is still possible.